Hygrothermal effects on mechanical joints prepared from fiber reinforced plastic nanocomposites. (November 2019) - Singh, Kulwinder; Saini, JS; Bhunia, H; Chowdhury, S Ray
The present work deals with the hygrothermal aging of the bolt joints prepared from glass fiber reinforced plastics. To investigate the effect of nanoclay on joint performance, nanoclay content was varied from 0 to 5 wt%, with laminates prepared from 3 wt% of nanoclay content demonstrating the best mechanical properties. Nanoclay acts as a mechanical interlock between the fiber and the epoxy and thus improves the interfacial bonding. A good dispersion of nanoclay also improves moisture barrier properties which in turn reduces the degradation of the composite material hygrothermal conditions. Bolt joints were prepared from woven glass fiber reinforced laminates incorporating 3 wt% of nanoclay content. To design the bolt joint, ASTM D5961 was used and the geometric parameters, i.e. edge distance to hole diameter (E/D) ratio and width to hole diameter (W/D) ratio were fixed to 5 and 6, respectively. Three different temperatures, i.e. 25℃, 50℃ and 75℃ were considered for the aging to three different duration of exposure, i.e. 1, 2 and 3 weeks. The effect of different levels of bolt torque, i.e. 0, 2 and 4 Nm were considered for the failure analysis of the joint. A full factorial design of experiment was conducted on important control factors, i.e. water temperature, exposure time, bolt torque and material variation. It was found that the hygrothermal conditions degraded the material with temperature as the most contributing factor.